EVALUATION OF DARN REPAIR FOR RECURRENCE RATE IN THE MANAGEMENT OF INDIRECT INGUINAL HERNIA - Kamran, Haider; Khan, Muhammad Asim; Rafiq, Muhammad Kashif; Khan, Amina Gul Shehzar; Waheed, Ayesha; Amin, Rabbia (Journal of Ayub Medical College Abbottabad, 2021)
Background: Management of Inguinal Hernia had long been remained an enigma & various methods had been employed for its management till date. Recent trend is towards the preferential use of mesh in open as well as Laparoscopic approaches where its advocates almost always undermine the role of raphys in the management of inguinal hernia but Darning repair despite all this critique is still a valid & viable option for the management of Indirect inguinal hernia. Methods: This descriptive study was designed & carried out at the surgical units of Ayub Teaching Hospital Abbottabad from February 01, 2016 to October 31, 2018. A total of 117 patients with indirect inguinal hernia (primary) were included in study, managed with Darn Repair & were later followed for 2 years for the evidence of recurrence. Results: None of the included patients (followed till last) whom underwent Darning Repair for Indirect Inguinal Hernia were found with the complication of recurrence till 02 years of follow-up although few patients were lost to follow-up for the whole duration 02 years and few others had suffered early complications like wound infection, seroma, haematoma formation, scrotal swelling or comparatively longer lasting post-operative pain. The Darn Repair was also found cost-effective as compared to Mesh repair. Conclusion: Darn Repair despite is a viable & effective option for Indirect Inguinal Hernia Repair (where its role indeed is prophylactic (NOT curative) against the future false recurrence), having no recurrence rate (as per our study results) like mesh repair (as per published literature) besides being reasonably cost-effective.